Deciphering the gene expression profile of peroxisome proliferator-activated receptor signaling pathway in the left atria of patients with mitral regurgitation. Issue 1 (December 2016) - Chen, Mien-Cheng; Chang, Jen-Ping; Lin, Yu-Sheng; Pan, Kuo-Li; Ho, Wan-Chun; Liu, Wen-Hao; Chang, Tzu-Hao; Huang, Yao-Kuang; Fang, Chih-Yuan; Chen, Chien-Jen
Abstract Background Differentially expressed genes in the left atria of mitral regurgitation (MR) pigs have been linked to peroxisome proliferator-activated receptor (PPAR) signaling pathway in the KEGG pathway. However, specific genes of the PPAR signaling pathway in the left atria of MR patients have never been explored. Methods This study enrolled 15 MR patients with heart failure, 7 patients with aortic valve disease and heart failure, and 6 normal controls. We used PCR assay (84 genes) for PPAR pathway and quantitative RT-PCR to study specific genes of the PPAR pathway in the left atria. Results Gene expression profiling analysis through PCR assay identified 23 genes to be differentially expressed in the left atria of MR patients compared to normal controls. The expressions of APOA1, ACADM, FABP3, ETFDH, ECH1, CPT1B, CPT2, SLC27A6, ACAA2, SMARCD3, SORBS1, EHHADH, SLC27A1, PPARGC1B, PPARA and CPT1A were significantly up-regulated, whereas the expression of PLTP was significantly down-regulated in the MR patients compared to normal controls. The expressions of HMGCS2, ACADM, FABP3, MLYCD, ECH1, ACAA2, EHHADH, CPT1A and PLTP were significantly up-regulated in the MR patients compared to patients with aortic valve disease. Notably, only ACADM, FABP3, ECH1, ACAA2, EHHADH, CPT1A and PLTP of the PPAR pathway were significantly differentially expressed in the MR patients compared to patients with aortic valve disease and normal controls. Conclusions Differentially expressed genes of the PPAR pathway have been identified in the left atria of MR patients compared with patients with aortic valve disease and normal controls.